Enhancing Akt Imaging through Targeted Reporter Expression - Limin Zhang; Mahaveer S. Bhojani; Brian D. Ross; Alnawaz Rehemtulla (Molecular Imaging)
The serine/threonine kinase PKB/Akt is a key mediator of survival and resistance to cancer therapy. Pharmacologic inhibition of Akt and its biologic sequelae may significantly impact the treatment of cancer. The use of molecular imaging technologies has contributed significantly to drug discovery research with an emphasis on drug efficacy, the mechanism of action, and target validation studies. We constructed a genetically engineered hybrid bioluminescent Akt reporter (BAR) molecule that reports on Akt serine/threonine kinase activity. Based on the fact that Akt is recruited to the plasma membrane on activation, we here describe a modified version of this reporter molecule (myristoylated and palmitoylated bioluminescent Akt reporter [MyrPalm-BAR]), which is membrane bound and whose bioluminescence activity can be used to monitor Akt activity at the cell membrane. Using changes in Akt activation status with small molecule inhibitors of Akt, we demonstrated that the membrane-targeted Akt reporter was more sensitive and quantitative. In addition, inhibition of upstream signaling kinases such as epidermal growth factor receptor and phosphatidylinositol 3-kinase activity resulted in changes in Akt activity that were quantitatively monitored by bioluminescence imaging. Based on these results, we propose that the membrane-associated Akt reporter may be better suited for identification of novel compounds that modulate the Akt pathway by high-throughput screening.